Cardiometabolic risk reductions in patients with type 2 diabetes mellitus newly treated with a sodium–glucose cotransporter 2 inhibitor versus a dipeptidyl peptidase‐4 inhibitor: A real‐world administrative database study in Japan. Issue 3 (14th December 2022) - Kashiwagi, Atsunori; Shoji, Shingo; Kosakai, Yoshinori; Koga, Tadashi; Asakawa, Keiko; Rokuda, Mitsuhiro
Abstract: Aims/Introduction: Sodium–glucose cotransporter 2 inhibitors (SGLT2i) have shown beneficial effects on cardiometabolic risk factors (hemoglobin A1c, body mass index, systolic blood pressure) in patients with type 2 diabetes mellitus. We compared combined cardiometabolic effects of SGLT2i on hemoglobin A1c, body mass index and systolic blood pressure versus dipeptidyl peptidase‐4 inhibitors (DPP4i) in Japanese patients with type 2 diabetes mellitus. Materials and Methods: This Japanese retrospective cohort study used the JMDC claims database. Patients newly treated with an SGLT2i ( n = 18, 936) or DPP4i ( n = 55, 484) were enrolled (January 2015–March 2020) and matched 1:1 using the propensity score. The primary end‐point was the proportion of patients achieving a composite outcome (i.e., simultaneous absolute/percent reduction in hemoglobin A1c ≥0.5%, body mass index ≥3% and systolic blood pressure ≥2 mmHg) 1 year after first SGLT2i or DPP4i prescription; Mantel–Haenszel common risk difference and its 95% confidence interval were estimated. Other end‐points included treatment persistence, with the associated hazard ratio calculated using the Cox proportional hazards model. Results: After matching, patient characteristics were balanced (7, 302 patients each). The proportion of patients achieving the composite outcome was significantly greater in patients receiving an SGLT2i than those receiving a DPP4i (31.0% [1, 279/4, 120] vs 12.9% [524/4, 070], risk difference 18.6%, 95% confidence interval 16.3, 20.9, P < 0.001). Risk of treatment discontinuation was significantly lower in the SGLT2i group than in the DPP4i group (hazard ratio 0.85, 95% confidence interval 0.81, 0.90, P < 0.001). Conclusions: In the present study, SGLT2i showed favorable cardiometabolic risk reduction and longer treatment persistence than DPP4i in Japanese patients with type 2 diabetes mellitus. Abstract : In this large retrospective cohort study using a Japanese administrative database, the proportion of patients with type 2 diabetes mellitus achieving a simultaneous improvement in hemoglobin A1c, body mass index and systolic blood pressure was significantly greater in patients newly treated with a sodium–glucose cotransporter 2 inhibitor than those newly treated with a dipeptidyl peptidase‐4 inhibitor. Furthermore, sodium–glucose cotransporter 2 inhibitor treatment showed better treatment persistence than dipeptidyl peptidase‐4 inhibitor treatment.